Transition-Metal-Free Synthesis of Quinoxalines from o-Phenylenediamines and Arylacetaldehydes under Basic Conditions - Song, Jinli; Li, Xiaolong; Chen, Yongxin; Zhao, Mingming; Dou, Yani; Chen, Baohua (Synlett, 2012)
A novel method for the synthesis of quinoxalines via transition-metal-free cyclization of o-phenylenediamine and arylacetaldehyde in a one-pot procedure has been developed. In this process, an inorganic base (K2CO3) is the only reagent required, and it proceeds smoothly in the absence of adding transition metal catalysts. The reaction appears to be very general and suitable for the construction of a variety of quinoxalines.
Keywords: quinoxalines; o-phenylenediamine; arylacetaldehyde; oxidation; condensation; transition-metal-free